Effect of body weight at photostimulation on productive performance and welfare aspects of commercial layers - Raziq, Fazal; Hussain, Jibran; Ahmad, Sohail; Asif Hussain, Muhammad; Khan, Muhammad Tahir; Ullah, Assad; Qumar, Muhammad; Wadood, Fazal; Gull-e-Faran (Animal Bioscience, 2024)
Objective: Due to current selection practices for increased egg production and peak persistency, the production profile, age at maturity, and body weight criteria for commercial layers are constantly changing. Body weight and age at the time of photostimulation will thus always be the factors that need to be adequately addressed among various production systems. The current study was carried out to determine the effects of pullets' body weight (low, medium, and heavy) on their performance, welfare, physiological response, and hormonal profile.Methods: With regard to live weight, 150 16-week-old pullets were divided into three groups using a completely randomized design (CRD) and held until the 50th week. One-way analysis of variance was used to evaluate the data under the CRD, and the least significant difference test was used to distinguish between treatment means.Results: In comparison to the medium and light birds, the heavy birds had higher body weight at maturity, an earlier age at maturity, and higher egg weight, eggshell weight, eggshell thickness, egg yolk index, breaking strength, egg surface area, egg shape index, egg volume, and hormonal profile except corticosterone. However, the medium and light birds had lower feed consumption rates per dozen eggs and per kilogram of egg mass than the heavy birds. Light birds showed greater body weight gain, egg production, and egg specific gravity than the other categories. At 20 weeks of age, physiological response, welfare aspects, and catalase were non-significant; however, at 50 weeks of age, all these factors—aside from catalase—were extremely significant.Conclusion: The findings of this study indicate that layers can function at lower body weights during photostimulation; hence, dietary regimens that result in lighter pullets may be preferable. Additionally, the welfare of the birds was not compromised by the lighter weight group.